Pengaruh Level Substitusi Rumput Bothriochloa Pertusa dengan Kangkung Terhadap pH, Konsentrasi Ammonia dan VFA Residu Fermentasi In Vitro - Olang, Buce Kornelis; Jelantik, I Gusti Ngurah; Nikolaus, Tara Tiba (Yayasan Sumber Daya Manusia Cerdas, 2025)
This study aims to determine the effect of the level of substitution of Bothriochloa Pertusa Grass with Kale on pH, Ammonia Concentration and In Vitro Fermentation Residue VFA. This study used the Analysis of Variance (Anova) procedure with 4 treatments and 4 periods as repetition. The treatments used were: P0: 60% bothriochloa grass + 40% Lamtoro, P1: 45% bothriochloa grass + 40% Lamtoro + 15% Kangkung, P2: 30% bothriochloa grass + 40% Lamtoro + 30% water spinach, P3: 15% Bothriochloa grass + 40% Lamtoro + 45% kale. Parameters measured were pH, NH3, VFA. The results of this study showed that the substitution of bothriochloa pertusa grass with water spinach had significant effects (P<0.05) on pH, the concentration of ammonia and VFA in residue of in vitro fermentation. The conclusion of this study is that the substitution of Bothriochloa pertusa grass with water spinach reduces pH and increases the concentration of ammonia and VFA the in vitro fermentation residue.